Pengaruh Strategi KWL (Know, Want, Learned) Terhadap Keterampilan Membaca Pemahaman Siswa Kelas V - Siskariani, Siskariani; Jamaluddin, Jamaluddin; Mega Isar Haura (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The problem in this research is how to apply the KWL (Knowing, Wanting, Learning) strategy to the reading comprehension skills of fifth grade students at SDN Pacinonggang Unggulan, Gowa Regency. This research aims to determine the effect of the KWL Strategy (Knowing, Wanting, Learning) on ​​the reading comprehension skills of class V at the superior Pacciongang Elementary School, Gowa Regency. The type of research used is an experiment in the form of a design experiment using a one group pretest-posttest design. The sample in this research was 25 class V students at SDN Pacciongang Unggulan Gowa Regency. Data collection was carried out using the results of the written assessment results. The data obtained was then explained using statistical analysis techniques, namely descriptive statistics and inferential statistics. After analyzing the data, the author found that student learning outcomes before using the outdoor learning learning method were relatively low, namely the average value of the Pretest results was 1,218, then the average value Posttest result is 1.984. After obtaining Tcount 10.5648 and Ttable 2.06390, we get tCount > tTable or 10, 5648 > 2.06390. Based on the results of tCount and tTable, it can be concluded that the use of the KWL (Know, Want, Learned) strategy on class students' reading comprehension ability V.